2012
DOI: 10.1007/s10750-012-1008-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasive zebra mussels on phytoplankton, turbidity, and dissolved nutrients in reservoirs

Abstract: Few experiments have quantified the effects of invasive zebra mussels (Dreissena polymorpha) on man-made reservoirs relative to other aquatic habitats. Reservoirs, however, are the dominate water body type in many of the states that are at the current front of the zebra mussel invasion into the western United States. The objective of this research, therefore, was to determine how zebra mussels affected phytoplankton, turbidity, and dissolved nutrients in water that was collected from three Kansas reservoirs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Dreissenids generally lead to a decline in phytoplankton and zooplankton biomass, whereas macrophytes and littoral zoobenthos increase (Higgins & Vander Zanden, ). Experiments have shown that the mussels might graze down cyanobacteria with their relatively large filtering capacity (Dionisio Pires et al ., ; Kirsch & Dzialowski, ). However, filtration of Dreissena on Microcystis ceased above a colony size threshold (White & Sarnelle, ).…”
Section: What Are the Plankton Dynamics During Prolonged Blooms?mentioning
confidence: 99%
“…Dreissenids generally lead to a decline in phytoplankton and zooplankton biomass, whereas macrophytes and littoral zoobenthos increase (Higgins & Vander Zanden, ). Experiments have shown that the mussels might graze down cyanobacteria with their relatively large filtering capacity (Dionisio Pires et al ., ; Kirsch & Dzialowski, ). However, filtration of Dreissena on Microcystis ceased above a colony size threshold (White & Sarnelle, ).…”
Section: What Are the Plankton Dynamics During Prolonged Blooms?mentioning
confidence: 99%
“…The zebra mussel is a prolific invasive bivalve, originating from the Black, Caspian and Azov Sea regions of central and eastern Europe. Several studies have focused on assessing the impact of the zebra mussel in its invaded range on existing algal communities 47 . A single zebra mussel filters approximately two litres of water per day 8 and significantly reduces the total biovolume of cyanobacteria in reservoir mesocosm experiments 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on assessing the impact of the zebra mussel in its invaded range on existing algal communities 47 . A single zebra mussel filters approximately two litres of water per day 8 and significantly reduces the total biovolume of cyanobacteria in reservoir mesocosm experiments 7 . Additionally, Smith et al ., (1998) measured a shift in dominance from cyanobacterial to diatom species when analysing changes in the cell density and taxonomic composition of phytoplankton assemblages in the freshwater portion of the Hudson River before and after the successful invasion of zebra mussels 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Researches for the phenomenon called hysteresis recently invoked marvelous, which even if the nutrient load to the lake is strongly reduced it could not recover its original clear state(Marten Scheffer & Nes, 2007). Lake sediments with higher TP will lead high P release and flux rate compared to sediments with low TP (Das et al, 2012).Sediment in shallow lake influence the water quality via perplexing mechanism, in which the benthic algae and sunshine may make a important role (Zhang et al, 2012;Kirsch & Dzialowski, 2012).Soluble reactive P and particulate P could be removed effectively from the shallow lake water or wetland with varying plant communities (Gu & Dreschel, 2008). Dredging looks like the available method to clarify eutrophic lake water for some peoples.…”
Section: Introductionmentioning
confidence: 99%